I'LL BE A TEACHER - Miller, Connie Colwell, 1976-; Baroncelli, Silvia (Mankato, MN : Amicus/Amicus Ink, 2019)
"Readers follow along on a day in the life of a kindergarten teacher as a young boy pretends to be a teacher while playing school with his sister. Includes a glossary and an activity that lets readers practice teaching skills"
Keywords: Teaching -- Juvenile literature. -- Vocational guidance; Teachers -- Juvenile literature